Activated protein C based therapeutic strategies in chronic diseases - Bock, Fabian; Shahzad, Khurrum; Vergnolle, Nathalie; Isermann, Berend (Thrombosis and Haemostasis, 2014)
Activated protein C (aPC) is a natural anticoagulant and a potent antiinflammatory and cytoprotective agent. At the expense of increased bleeding risk aPC has been used – with some success – in sepsis. The design of cytoprotective-selective aPC variants circumvents this limitation of increased bleeding, reviving the interest in aPC as a therapeutic agent. Emerging studies suggest that aPC’s beneficial effects are not restricted to acute illness, but likewise relevant in chronic diseases, such as diabetic nephropathy, neurodegeneration or wound healing. Epigenetic regulation of gene expression, reduction of oxidative stress, and regulation of ROS-dependent transcription factors are potential mechanisms of sustained cytoprotective effects of aPC in chronic diseases. Given the available data it seems questionable whether a unifying mechanism of aPC dependent cytoprotection in acute and chronic diseases exists. In addition, the signalling pathways employed by aPC are tissue and cell specific. The mechanistic insights gained from studies exploring aPC’s effects in various diseases may hence lay ground for tissue and disease specific therapeutic approaches. This review outlines recent investigations into the mechanisms and consequences of long-term modulation of aPC-signalling in models of chronic diseases.
Keywords: Signal transduction; protein C/S pathway; diabetes mellitus; coagulation factors; chronic diseases